A multi-gene dataset reveals a tropical New World origin and Early Miocene diversification of croakers (Perciformes: Sciaenidae) - Lo, P.-C.; Liu, S.-H.; Chao, N.L.; Nunoo, F.K.E.; Mok, H.-K; Chen, W.-J. (Molecular Phylogenetics and Evolution, 2015)
Widely distributed groups of living animals, such as the predominantly marine fish family Sciaenidae, have always attracted the attention of biogeographers to document the origins and patterns of diversification in time and space. In this study, the historical biogeography of the global Sciaenidae is reconstructed within a molecular phylogenetic framework to investigate their origin and to test the hypotheses explaining the present-day biogeographic patterns. Our data matrix comprises six mitochondrial and nuclear genes in 93 globally sampled sciaenid species from 52 genera. Within the inferred phylogenetic tree of the Sciaenidae, we identify 15 main and well-supported lineages; some of which have not been recognized previously. Reconstruction of habitat preferences shows repeated habitat transitions between marine and euryhaline environments. This implies that sciaenids can easily adapt to some variations in salinity, possibly as the consequence of their nearshore habitats and migratory life history. Conversely, complete marine/euryhaline to freshwater transitions occurred only three times, in South America, North America and South Asia. Ancestral range reconstruction analysis concomitant with fossil evidence indicates that sciaenids first originated and diversified in the tropical America during the Oligocene to Early Miocene before undergoing two range expansions, to Eastern Atlantic and to the Indo-West Pacific where a maximum species richness is observed. The uncommon biogeographic pattern identified is discussed in relation to current knowledge on origin of gradients of marine biodiversity toward the center of origin hypothesis in the Indo-West Pacific.
Keywords: Biogeography; Indo-West Pacific; New World; Sciaenidae; Systematics; Time-calibrated phylogeny